2012
DOI: 10.1152/ajpheart.00532.2011
|View full text |Cite
|
Sign up to set email alerts
|

Normal pregnancy: mechanisms underlying the paradox of a ouabain-resistant state with elevated endogenous ouabain, suppressed arterial sodium calcium exchange, and low blood pressure

Abstract: Endogenous cardiotonic steroids (CTS) raise blood pressure (BP) via vascular sodium calcium exchange (NCX1.3) and transient receptor-operated channels (TRPCs). Circulating CTS are superelevated in pregnancy-induced hypertension and preeclampsia. However, their significance in normal pregnancy, where BP is low, is paradoxical. Here we test the hypothesis that vascular resistance to endogenous ouabain (EO) develops in normal pregnancy and is mediated by reduced expression of NCX1.3 and TRPCs. We determined plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 55 publications
4
42
0
Order By: Relevance
“…In agreement with previous studies, 15,21 we found higher levels of circulating ouabain in pregnant women ( Figure 10A). However, no significant differences in the steroid concentration were found at the different times tested.…”
Section: Abundance Of Circulating Ouabain In Human Fetal and Maternalsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies, 15,21 we found higher levels of circulating ouabain in pregnant women ( Figure 10A). However, no significant differences in the steroid concentration were found at the different times tested.…”
Section: Abundance Of Circulating Ouabain In Human Fetal and Maternalsupporting
confidence: 93%
“…First, circulating ouabain levels were determined in nonpregnant and pregnant mice. As shown in other studies, 15 the levels of the steroid are increased by .3-fold during pregnancy (Figure 2). Notably, because the determination of ouabain is based on the interaction with antibodies, immunoreactive material is actually being measured.…”
Section: Reduction In Maternal Circulating Ouabain Reduces Offspringsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, mice with one null ␣ 1 -allele (␣ 1 ϩ/Ϫ ) express many fewer total Na ϩ pumps in ASMCs (ϳ60% of normal) but have normal basal BP (57). In addition, plasma EO is elevated in many humans with essential hypertension or mineralocorticoid hypertension (33,39,49), in several rodent hypertension models (14,15,24,27), and in pregnant rats (19). Indeed, prolonged ouabain administration induces hypertension in rodents (11,12,34).…”
mentioning
confidence: 99%
“…Circulating levels of ouabain are increased during pregnancy. 82 Patients with renal failure have increased levels of endogenous CTS, and there is evidence that the high levels of CTS may be deleterious for the cardiovascular system. This would particularly be the case for patients who have also been given CTS drugs.…”
Section: Protective Effects Of Namentioning
confidence: 99%